2018
DOI: 10.1002/mnfr.201700665
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomic Screen Reveals Changes in Human Plasma Metabolite Profiles Following Consumption of Fresh Broccoli Sprouts

Abstract: This investigation identifies several potential molecular targets of crucifers that may aid in studying established and emerging health benefits of consuming cruciferous vegetables and related bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Previously, a small clinical study reported changes in plasma fatty acids and GSH/GSH component levels after even a single meal of broccoli sprouts, similar to pathways we report here for rat plasma [29]. Differences in findings might be due to the shorter duration of the clinical study.…”
Section: Discussionsupporting
confidence: 82%
“…Previously, a small clinical study reported changes in plasma fatty acids and GSH/GSH component levels after even a single meal of broccoli sprouts, similar to pathways we report here for rat plasma [29]. Differences in findings might be due to the shorter duration of the clinical study.…”
Section: Discussionsupporting
confidence: 82%
“…This software allows for the correction of metabolite intensity with the intensity of the internal standards. Data obtained with MultiQuant was imported into MarkerView software (AB SCIEX) for initial data visualization [52]. Student’s t-tests were performed with GraphPad Prism Software (GraphPad, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Raw data from un-targeted lipidomic analysis was imported into Progenesis QI software (Version 2.3, Nonlinear Dynamics, Waters) in order to perform data normalization, feature detection, peak alignment, and peak integration [52]. A repeated measure analysis of variance (ANOVA) was also performed using Progenesis QI software in order to identify significantly alter features [52]. Similarly, we obtained the q -values based on the p -values in order to adjust for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Fascinatingly, underlying mechanisms and key molecular targets involved in the ability of cruciferous vegetables to improve human health have been characterized through plasma metabolite profiles before and after human consumption of broccoli sprouts. The investigation identified several potential molecular targets of crucifers, including fatty acids, glutathione, glutamine, cysteine, dehydroepiandrosterone, and deoxyuridine monophosphate, aiding in the study of established and emerging health benefits that the consumption of cruciferous vegetables may possess . It is apparent that future research utilizing metabolomics and its integration with additional –omics technologies has strong potential of helping both the fields of bladder cancer and isothiocyanates significantly advance.…”
Section: Future Approachesmentioning
confidence: 99%